Diagnóstico ambiental, prospecção tecnológica e proposição de um novo modelo de gestão de cadáveres - Zandoná, Daiane Miglioli (2019)
Although there are various types of cemeteries, the most common are the traditional cemeteries and park cemeteries, in which the usual characteristics of burial are inhumations or the use of graves, fragile forms that, by times, end up being a risk to the environment, since, after being buried, the human body goes through a series of natural transformations, during which it releases a compound known as necro-leachate that has great potential of environmental contamination, being a risk to soil contamination and mainly to underground water. In order to minimize the risk of contamination, implantation, operation and administration rules of cemeteries should be followed. This study has as objective the diagnosis of the traditional corpse management forms, by the qualitative and quantitative estimation of the waste generating sources and the proposition of a new model of management of corpses based on new technologies, having as a study element the municipality of Cascavel-PR. In the methodology, besides the characterization of residual generating sources, it was prospected usual technologies and new technologies utilized in the management of corpses and to the proposition of a new management model. The most relevant results demonstrated that, in the period of 2010 to 2015, in the municipality of Cascavel-Pr, the total of live births was of 29.103, the quantity of female and male deaths totaled 16,519 people, generating the cumulative amount of 1,356 tons of waste. From this total, it is estimated that 738 tons correspond to liquid waste and 618 tones to solid waste. It was found that, yet, the existence of inert material (1,74 tons) consisting of bones, nails, hair and teeth. From the general point of view, by the contamination potential it was verified that the traditional corpse management model has collapsed. In this way a new management model was proposed based in the “pyrolysis in anaerobic environment” as alternative technology. This new model allows the use of corpses in symphony with territorial development, sustainable and innovating, suggesting, at the same time, the need for change in cultural and religious paradigms, being these ones, big barriers to the acceptance of new forms of human body destination after death.